2021
DOI: 10.1136/bmjopen-2021-048789
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden and proxy-reported outcomes of people without natural speech: a cross-sectional survey study

Abstract: ObjectiveTo examine interrelations between care-related burden on informal caregivers and their proxy assessments of outcomes in people without natural speech.DesignA cross-sectional survey.SettingData were collected in January 2019 from a postal survey of informal caregivers of people without natural speech who are insured by a large regional health insurance company in the German federal state of Lower Saxony.Participantsn=714 informal caregivers of people without natural speech of all ages and with various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…22,40,41 Consequently, interventions should not only consider the needs of the AAC users, but also those of the informal caregivers. 42 In this regard, our study results indicate that the intervention positively influenced participation in AAC care as well as informal caregivers' openness towards AAC by involving them in all elements of the intervention and keeping them informed about the AAC user's development.…”
Section: Discussionmentioning
confidence: 64%
“…22,40,41 Consequently, interventions should not only consider the needs of the AAC users, but also those of the informal caregivers. 42 In this regard, our study results indicate that the intervention positively influenced participation in AAC care as well as informal caregivers' openness towards AAC by involving them in all elements of the intervention and keeping them informed about the AAC user's development.…”
Section: Discussionmentioning
confidence: 64%
“…Close family members or proxy professionals tend to be capable proxies, although proxy reports may be influenced by caregiving burden, especially for those who provide care to older adults or to people with chronic diseases/health condition. Proxy ratings of disability increased with caregiving hours and higher perceived burden, and proxies reporting more burden tended to report more patient impairment [ 20 , 59 ]. Evidence showed that caregiver burden may result in misleading representation of the older person’s functional status, specifically in regard to instrumental activities of daily living (IADL) items [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…The group of people who use AAC is heterogeneous in terms of age, disability, and the extent of physical, intellectual, and communication limitations [ 14 ]. In a cross-sectional study, we have already found significant interrelations between caregiver burden and caregiver assessment of the health-related quality of life and functioning of people without natural speech [ 15 ]. Although it is unclear whether (1) higher burden leads to poorer above-mentioned outcomes for people without natural speech, (2) whether poor outcomes lead to higher burden, or (3) only the assessment of these outcomes is affected, the results can be seen as an indication of the major importance of burden in this care context.…”
Section: Introductionmentioning
confidence: 99%